In vitro antiplasmodium and chloroquine resistance reversal effects of andrographolide - Ibraheem, Zaid Osamah; Abd. Majid, Roslaini; Mohd Sidek, Hasidah; Md Noor, Sabariah; Yam, Mun Fei; Abd Rachman Isnadi, Mohammad Faruq; Basir, Rusliza (Hindawi Limited, 2019)
The emergence of drug-resistant strains of Plasmodium falciparum is the worst catastrophe that has ever confronted the dedicated efforts to eradicate malaria. This urged for searching other alternatives or sensitizers that reverse chloroquine resistance. In this experiment, the potential of andrographolide to inhibit plasmodial growth and reverse CQ resistance was tested in vitro using the SYBRE green-1-based drug sensitivity assay and isobologram technique, respectively. Its safety level toward mammalian cells was screened as well against Vero cells and RBCs using MTT-based drug sensitivity and RBC hemolysis assays, respectively. Its effect against hemozoin formation was screened using β-hematin formation and heme fractionation assays. Its molecular characters were determined using the conventional tests for the antioxidant effect measurement and the in silico molecular characterization using the online free chemi-informatic Molinspiration software. Results showed that andrographolide has a moderate antiplasmodium effect that does not entitle it to be a substituent for chloroquine. Furthermore, andrographolide ameliorated the sensitivity of the parasite to chloroquine. Besides, it showed an indirect inhibitory effect against hemozoin formation within the parasite and augmented the chloroquine-induced inhibition of hemozoin formation. The study suggests that its chloroquine resistance reversal effect may be due to inhibition of chloroquine accumulation or due to its impact on the biological activity of the parasite. Overall, this in vitro study is a clue for the reliability of andrographolide to be added with chloroquine for reversal of chloroquine resistance and tolerance, but further in vivo studies are recommended to confirm this notion. In spite of its prominent and safe in vitro and in vivo growth inhibitory effect and its in vitro chloroquine resistance reversing effect, it is inapplicable to implement it in malaria chemotherapy to substitute chloroquine or to reverse its resistance.